How beliefs, knowledge and intuition affect the way we search? Examining how users formulate search queries about climate change - Vziatysheva, Victoria; Makhortykh, Mykola; Sydorova, Maryna; Jumle, Vihang (AoIR Selected Papers of Internet Research, 2026)
Search engines are one of the most common ways for users to discover news and political information. As a result, the content and sources prioritized by these platforms are of paramount importance. Previous research has shown that search engines can provide biased outputs by, for example, discriminating against certain social groups or favoring certain viewpoints. However, there has been a gap in understanding how users search for information using these systems and, in particular, how they formulate their search queries. Yet the choice of query is crucial, as it largely determines the information users are exposed to, and thus may lead to particular biases. To address this gap, we conducted a representative survey of Swiss citizens (N = 1,070) in which we investigate how voters search for information about an environmental popular initiative that was voted on in Switzerland in February 2025. In particular, we test the assumption that selective exposure (or the tendency to prefer information that confirms one’s own beliefs) is more pronounced when users are presented with a limited number of options (e.g., search engine autocomplete suggestions) than when they formulate them independently. We also examine how pre-existing knowledge about the topic, beliefs about climate change, political attitudes, and cognitive factors affect query formulation. This study contributes to existing research by demonstrating how individual characteristics of users can influence information seeking behavior and how selective exposure can manifest itself under different search conditions.